WHAT TRANSLATION TELLS US ABOUT MOTION: A CONTRASTIVE STUDY OF TYPOLOGICALLY DIFFERENT LANGUAGES - Ibarretxe, Iraide (International Journal of English Studies, 2003)
Slobin (1991, 1996a,b, 1997) has argued that the typological differences between languages with either a satellite-framed or a verb-framed lexicalisation pattern (Talmy, 2000) have importantdiscourse and rhetorical consequences for the expression of 'paths of movement' and 'mannerof movement'. These differences are especially significant for the translator since s/he has toadapt the rhetorical style of the source language to that of the target language. According toSlobin (1996a, 2000, ms.), the major difference lies in the loss or gain of information about pathand manner specifications during the translation process.We will focus on three languages,English (satellite-framed), Spanish and Basque (both verb-frarned but with important intratypological differences). Basing ourselves on data from translations of the same English text(Tolkien's The Hobbit) into these two target languages, we will compare and analyse in detailthe different strategies that Spanish and Basque translators follow when adapting the English textto the stylistic and typological characteristics of their own languages.